Chylous ascites following retroperitoneal lymphadenectomy in gynecologic malignancies: Incidence, risk factors and management. (April 2015) - Solmaz, Ulas; Turan, Volkan; Mat, Emre; Dereli, Murat Levent; Ekin, Atalay; Peker, Nuri; Tosun, Gokhan; Dogan, Askin; Gokcu, Mehmet; Sanci, Muzaffer
Abstract: Introduction: Chylous ascites is a rare form of ascites that results from accumulated lymph fluid in the peritoneal cavity caused by blocked or disrupted lymph flow through the major lymphatic channels. In the present study, our aim was to analyze the incidence, risk factors, diagnostic evaluation and management of chylous ascites after lymphadenectomy in gynecologic malignancies. Methods: A total of 458 patients who had undergone staging surgery for gynecologic malignancies at our institution between January 2010 and December 2013 were retrospectively reviewed. After the exclusion criteria were applied, 399 patients were divided into 2 groups based on the presence (n = 36) or absence (n = 363) of chylous ascites. Results: Among the 399 patients, 36 (9%) developed chylous ascites. The median time to onset was 4 days (range, 2–7 days). The analysis of the various features of lymphadenectomy showed that the number of para-aortic lymph nodes (PALNs) removed was significantly greater in the patients with chylous ascites (p < 0.001). A cut-off value of >14 PALNs was a good predictor of chylous ascites. In all patients, chylous ascites resolved with conservative management. Conclusions: Postoperative chylous ascites was strongly associated with the number of harvested PALNs. According to our findings, we suggest that conservative treatment should be the first step in managing patients with chylous ascites. Using an abdominal drain after surgery seems to be an effective diagnostic tool and treatment method for chylous ascites. Highlights: Postoperative chylous ascites incidence is mostly related to extensive and meticulous paraaortic lymphadenectomy. Chylous ascites cases generally respond well to conservative management. Abdominal drain is an effective diagnostic tool and treatment method for chylous ascites.